Efficacy of 5mg Versus 10mg Olanzapine for Prevention of Highly Emetogenic Chemotherapy Induced Nausea & Vomiting: A Randomized Phase II Study from Nepal - KC, Anuj; Thapa, Sudip; Paudel, Bishnu Dutta; Sharma, Rajeev; Shilpakar, Ramila (Annapurna Journal of Health Sciences, 2025)
Introduction: The most common side effects of chemotherapy are nausea and vomiting. Olanzapine is one of the important drug used as a prophylaxis for the prevention of chemotherapy-induced nausea and vomiting. It is important to know the efficacy and toxicity of low-dose (OLD) compared to standard-dose (OSD) olanzapine for the prevention of chemotherapy-induced nausea and vomiting caused by highly emetogenic chemotherapy. Methods: A randomized study was conducted for this study where patients were randomly assigned to receive either OSD or OLD orally. Both groups received dexamethasone and granisetron intravenously before chemotherapy. Patients were asked to record daily episodes of nausea and vomiting/retching, the intensity of symptoms, and the need for rescue therapy. Data were analyzed using an independent t-test to compare the mean proportions between two doses of olanzapine. The frequency was analyzed using descriptive statistics. Results: In this study, each group contained 48 patients. There was an absence of nausea (95.83% vs. 87.50%; p= 0.33), acute vomiting (93.75% vs. 95.83%; p= 0.64), and delayed vomiting (91.66% vs. 93.75%; p= 0.69) between OLD and OSD. Complete response was (89.58% vs 89.58% ; p=1.00) and total control was (87.50% vs 79.16% ; p= 0.27) between OLD and OSD respectively. Rescue therapy was required in 8.33% of patients in each group. No significant differences in toxicities were noted between treatment arms. Conclusion: OLD had comparable efficacy and toxicity compared to OSD in the management of CINV, Hence, OLD could be effective and cheap prophylaxis for CINV against HEC in low-resource countries.